2009
DOI: 10.1021/bi802332j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigations of Human Reticulocyte 15- and Platelet 12-Lipoxygenases with Arachidonic Acid

Abstract: Human reticulocyte 15-lipoxygenase-1 (15-hLO-1) and human platelet 12-lipoxygenase (12-hLO) have been implicated in a number of diseases, with differences in their relative activity potentially playing a central role. In the current paper, we characterize the catalytic mechanism of these two enzymes with arachidonic acid (AA) as the substrate. Using variable-temperature kinetic isotope effects (KIE) and solvent isotope effects (SIE), we demonstrate that both kcat/Km and kcat for 15-hLO-1 and 12-hLO involve mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 47 publications
12
54
0
Order By: Relevance
“…Iron concentrations were compared with standardized iron solutions and used to normalize enzyme concentrations. Protein expression yields and iron content of 12-LOX were similar to previously published results ( 31,32 ).…”
Section: Overexpression and Purifi Cation Of 12-loxsupporting
confidence: 88%
See 1 more Smart Citation
“…Iron concentrations were compared with standardized iron solutions and used to normalize enzyme concentrations. Protein expression yields and iron content of 12-LOX were similar to previously published results ( 31,32 ).…”
Section: Overexpression and Purifi Cation Of 12-loxsupporting
confidence: 88%
“…Although AA makes up a large proportion of the phospholipid content, other fatty acids are also available from the platelet membrane, and their content, relative to AA, has been shown to fl uctuate depending on diet ( 27,29,30 ). Whereas the catalysis of 12-LOX with AA has been studied previously ( 19,21,31,32 ), little is known about the relative 12-LOX kinetic rates of the other fatty acid substrates and their physiological effects on platelet activation. LOX are known to have promiscuous substrate selectivity and can react with a variety of fatty acids, ranging from 18 to 22 carbons long and having 2 to 6 sites of unsaturation.…”
Section: Steady-state Kinetic Measurementsmentioning
confidence: 99%
“…In the present study, we found that the activation energies for PGHS-1 or -2 with 10,10,13,13-d 4 -AA (d 4 -AA) are smaller than that for PGHS-1 or -2 with AA and therefore KIEs for PGHS increase with the temperature, showing abnormal, or inverted, temperature dependence. There are only a few reported examples of KIE values increasing with temperature in chemical reactions [23][24][25][26][27] and enzymatic catalyses [16,28].…”
Section: Methodsmentioning
confidence: 99%
“…N544 in hp-12LOX might be at a longer distance but geometrically in a proper place of the iron's coordination polyhedron, and participating in a tightly woven hydrogen bonding network, like in soybean enzymes (24) where the role of this residue was extensively studied (25,26). Human lipoxygenases 5-, 12S-12R-and eLOX3 have Asn while 15-LOX has His in type 1 and Ser in type 2, which might contribute to their so remarkably different behavior (27,28). We do not know a high resolution structure of any human lipoxygenase except an engineered catalytic domain of hp-12LOX depicted on Fig.…”
Section: -------------------------------------------------mentioning
confidence: 99%
“…3). They all could be allosteric although their kinetic properties might be different (28,31,32). Bearing that in mind and the fact that each molecule of hp-12LOX can bind to 3 molecules of substrate/product one can presume that any changes in self-association would impinge on the enzymatic activity.…”
Section: -------------------------------------------------mentioning
confidence: 99%